Novel cryoballoon ablation system for pulmonary vein isolation: multicenter assessment of efficacy and safety-ANTARCTICA study - Heeger, Christian-H; Pott, Alexander; Sohns, Christian; Riesinger, Lisa; Sommer, Philipp; Gasperetti, Alessio; Tondo, Claudio; Fassini, Gaetano; Moser, Fabian; Lucas, Philipp; Weinmann, Karolina; Bohnen, Jan-Eric; et al. (EP Europace, 2022)
Aims Pulmonary vein isolation (PVI) either by balloon devices or radiofrequency forms the cornerstone of invasive atrial fibrillation (AF) treatment. Although equally effective cryoballoon (CB)-based PVI offers shorter procedure duration and a better safety profile. Beside the worldwide established Arctic Front Advance system, a novel CB device, POLARx, was recently introduced. This CB incorporates unique features, which may translate into improved efficacy and safety. However, multicentre assessment of periprocedural efficacy and safety is lacking up to date. Methods and results A total of 317 patients with paroxysmal or persistent AF were included and underwent POLARx CB-based PVI in 6 centres from Germany and Italy. Acute efficacy and safety were assessed in this prospective multicenter observational study. In 317 patients [mean age: 64 +/- 12 years, 209 of 317 (66%) paroxysmal AF], a total of 1256 pulmonary veins (PVs) were identified and 1252 (99,7%) PVs were successfully isolated utilizing mainly the short tip POLARx CB (82%). The mean minimal CB temperature was -57.9 +/- 7 degrees C. Real-time PVI was registered in 72% of PVs. The rate of serious adverse events was 6.0% which was significantly reduced after a learning curve of 25 cases (9.3% vs. 3.0%, P = 0.018). The rate of recurrence-free survival after mean follow-up of 226 +/- 115 days including a 90-day blanking period was 86.1%. Conclusion In this large multicentre assessment, the novel POLARx CB shows a promising efficacy and safety profile after a short learning curve.